Factors associated with school performance in the NCEE a policy study - Barsaga, Eligio B. 1945- (1977)
Student socioeconomic and student academic backgrounds and community school characteristics were investigated concerning students drawn from the 75 secondary schools in the Division of Angeles City and Pampanga who took the 1975 National College Entrance Examination. School performance in the NCEE is a function of the four input factors investigated. The best single determinant is college-educated mothers, followed by the extent of adequacy of equipment and supplies in science and mathematics laboratories and percentage of students planning to be self-supporting in college. High-scoring schools in general have a higher proportion of students with (a) professional and college-educated fathers, (b) college-educated mothers and (c) students with high family income than do low-scoring schools.
Mimeographed.
Vita.
Thesis (D.Ed.)--University of the Philippines, Diliman.
Keywords: Universities and colleges -- Philippines -- Examinations